Hubungan antara Tingkat Kecemasan dengan Kualitas Hidup pada Pasien Chronic Kidney Disease (CKD) yang Menjalani Hemodialisis di RSD dr. Soebandi Jember (Correlation between the Level of Anxiety and Quality of Life of Chronic Kidney Disease (CKD) Patients - Novita Dwi Cahyani,; Justina Evy Tyaswati; Dwita Aryadina Rachmawati (Pustaka Kesehatan, 2016)
Chronic Kidney Disease (CKD) is a chronic disease that results in the progressive decline in renal function and irreversible. Patients with end stage CKD requiring hemodialysis therapy. CKD patients who undergo hemodialysis therapy largely experiencing symptoms of anxiety and changes in quality of life. The aim of this study was to determine the correlation between the anxiety level and the quality of life of patients with CKD during hemodialysis therapy at dr. Soebandi Regional Hospital Jember. Research using Cross Sectional Design with the total number of respondents as many as 30 people and was carried out in November 2015. The respondent's anxiety level was measured using a HARS questionnaire and assessment of quality of life using the WHOQOL-BREF questionnaire. The results revealed respondents with mild anxiety were 16,67% (10% with good quality of life and 6,67% with bad quality of life), respondents with moderate anxiety were 40% (10% with good quality of life and 30% with bad quality of life), and respondents with severe anxiety were 43,33% with bad quality of life. Spearman correlation test showed the significance (p) 0,00 with correlation coefficient (r) – 0,517. Thus, it can be concluded that there was a correlation between the level of anxiety and quality of life of CKD patients during hemodialysis therapy at dr.Soebandi Regional Hospital Jember.   Keywords: Chronic Kidney Disease (CKD), hemodialysis, anxiety, quality of life.